Review of Sharia Economic Law on Termination of Agricultural Land Lease Contract in Alahan Panjang - Sari Fitri (Budapest International Research and Critics University, 2022)
This study aims to find out the economic fiqh review of the termination of agricultural land lease contracts in Alahan Panjang. Renting farmland is done during the growing season until the harvest season in Alahan Panjang. The formulation of the problem in this study is how the implementation of the termination of agricultural land lease contracts in Alahan Panjang and how the economic fiqh review of the termination of agricultural land lease contracts. This study uses field research with qualitative approach. The data was obtained through in-depth interviews. Based on the results of the study concluded the implementation of agricultural land lease contracts have not met the pillars and conditions, namely the unilateral termination of agricultural land lease contracts from Mu'ajir while the time agricultural land contract has not expired. Termination of this contract results in material losses for musta'jir. In this economic fiqh review is a bad habit or urf' fasid. There is no benefit of both parties in the termination of the land lease contract, because one of the parties feels harmed.